The role and effectiveness of tour guide in influencing tourist behaviour - Syed Jaafar, Syed Muhammad Rafy (2013)
Research about the problems that occur in the interpretation spectrum has a lot been done, but still less study of the relationship between interpretation techniques and tourists experience needs while selecting the destination as a holiday destination. This study was conducted to understand the extent to which the role of interpretation (tour guide) in educating the tourists about conservation awareness. Pahang National Park becomes the study area because it is one of the areas that have a best nature tour guide in Malaysia. Quantitative and qualitative techniques are used because it is able to understand the relationship between the role of interpretation and tourists, more depth. This study will measure the quality of tour guides whether they are eligible to provide information or education on conservation to the tourists. Furthermore, this study will also determine whether the tourists do not really want to be educated about conservation or the quality of tour guides do not achieve the quality of required level. The findings show international and domestic tourists actually really want to be educated about conservation when they visit the National Park, but the quality of tour guides still do not reach the level needed. Factors cause the poor quality of guides that found in this study be seen will help in planning the development of the tourism industry in providing effective technical interpretation (tour guides) to tourists in the future.